Learning from the Past and Stepping into the Future: Toward a New Generation of Conflict Prediction1. Issue 4 (21st November 2013) - Ward, Michael D.; Metternich, Nils W.; Dorff, Cassy L.; Gallop, Max; Hollenbach, Florian M.; Schultz, Anna; Weschle, Simon
Abstract : Developing political forecasting models not only increases the ability of political scientists to inform public policy decisions, but is also relevant for scientific advancement. This article argues for and demonstrates the utility of creating forecasting models for predicting political conflicts in a diverse range of country settings. Apart from the benefit of making actual predictions, we argue that predictive heuristics are one gold standard of model development in the field of conflict studies. As such, they shed light on an array of important components of the political science literature on conflict dynamics. We develop and present conflict predictions that have been highly accurate for past and subsequent events, exhibiting few false‐negative and false‐positive categorizations. Our predictions are made at the monthly level for 6‐month periods into the future, taking into account the social–spatial context of each individual country. The model has a high degree of accuracy in reproducing historical data measured monthly over the past 10 years and has approximately equal accuracy in making forecasts. Thus, forecasting in political science is increasingly accurate. At the same time, by providing a gold standard that separates model construction from model evaluation, we can defeat observational research designs and use true prediction as a way to evaluate theories. We suggest that progress in the modeling of conflict research depends on the use of prediction as a gold standard of heuristic evaluation.